Omics-assisted characterization of two-component system genes from Gossypium Raimondii in response to salinity and molecular interaction with abscisic acid - Rasool, Asima; Azeem, Farrukh; Ur-Rahman, Mahmood; Rizwan, Muhammad; Hussnain Siddique, Muhammad; Bay, Daniyah Habiballah; Binothman, Najat; Al Kashgry, Najla Amin T.; Qari, Sameer H. (Frontiers in Plant Science, 2023)
The two-component system (TCS) genes are involved in a wide range of physiological processes in prokaryotes and eukaryotes. In plants, the TCS elements help in a variety of functions, including cell proliferation, response to abiotic and biotic stresses, leaf senescence, nutritional signaling, and division of chloroplasts. Three different kinds of proteins make up the TCS system in plants. These are known as HKs (histidine kinases), HPs (histidine phosphotransfer), and RRs (response regulators). We investigated the genome of Gossypium raimondii and discovered a total of 59 GrTCS candidates, which include 23 members of the HK family, 8 members of the HP family, and 28 members of the RR family. RR candidates are further classified as type-A (6 members), type-B (11 members), type-C (2 members), and pseudo-RRs (9 members). The GrTCS genes were analyzed in comparison with the TCS components of other plant species such as Arabidopsis thaliana, Cicer arietinum, Sorghum bicolor, Glycine max, and Oryza sativa. This analysis revealed both conservation and changes in their structures. We identified 5 pairs of GrTCS syntenic homologs in the G. raimondii genome. All 59 TCS genes in G. raimondii are located on all thirteen chromosomes. The GrTCS promoter regions have several cis-regulatory elements, which function as switches and respond to a wide variety of abiotic stresses. RNA-seq and real-time qPCR analysis showed that the majority of GrTCS genes are differentially regulated in response to salt and cold stress. 3D structures of GrTCS proteins were predicted to reveal the specific function. GrTCSs were docked with abscisic acid to assess their binding interactions. This research establishes the groundwork for future functional studies of TCS elements in G. raimondii, which will further focus on stress resistance and overall development.